2022
DOI: 10.3390/ijms232315208
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Neurofilament Light Chain (NF-L) Is a Prognostic Biomarker for Cortical Damage Evolution but Not for Cognitive Impairment or Epileptogenesis Following Experimental TBI

Abstract: Plasma neurofilament light chain (NF-L) levels were assessed as a diagnostic biomarker for traumatic brain injury (TBI) and as a prognostic biomarker for somatomotor recovery, cognitive decline, and epileptogenesis. Rats with severe TBI induced by lateral fluid-percussion injury (n = 26, 13 with and 13 without epilepsy) or sham-operation (n = 8) were studied. During a 6-month follow-up, rats underwent magnetic resonance imaging (MRI) (day (D) 2, D7, and D21), composite neuroscore (D2, D6, and D14), Morris-wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 66 publications
0
14
0
Order By: Relevance
“…Across multiple models of single TBI, including closed head injury, controlled cortical impact, penetrating injury, blast injury and CHIMERA, NfL peaks in the days following injury ( Fig. 4A-C ) (7,39,40,46,50,52), with an injury-severity-dependent elevation (7) indicating that axonal injury/damage is a common pathophysiological mechanism. Notably, following rmTBI, NfL responds to cumulative injuries (45,46,49) and injury intervals (45,47), suggesting that NfL levels could inform on susceptibility to subsequent mild TBIs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Across multiple models of single TBI, including closed head injury, controlled cortical impact, penetrating injury, blast injury and CHIMERA, NfL peaks in the days following injury ( Fig. 4A-C ) (7,39,40,46,50,52), with an injury-severity-dependent elevation (7) indicating that axonal injury/damage is a common pathophysiological mechanism. Notably, following rmTBI, NfL responds to cumulative injuries (45,46,49) and injury intervals (45,47), suggesting that NfL levels could inform on susceptibility to subsequent mild TBIs.…”
Section: Discussionmentioning
confidence: 99%
“…The overall temporal pattern of NfL blood levels closely aligns with studies in gyroencephalic models in pigs (109), and with the human data (7,20). However, there is a difference in the time-to-first-peak between rodents (days 1-3, (39,40,52)), pigs (days 5-10,(109)), and humans (days 14-21; (20)) ( Fig. 5 ), possibly related to species-specific differences in protein turnover rates or clearance mechanisms (110), anatomical differences in white matter (111), and differences in BBB dysfunction or permeability (112).…”
Section: Discussionmentioning
confidence: 99%
“…The molecular pathways through which NfL participates are mainly addressing the structural integrity of the neuronal cytoskeleton. Despite being an intracellular structural constituent of neurons, NfL could also be found in synaptic space, where they supposedly interact with NMDA GluN1 receptors by influencing their distribution [ 38 ]. Their local or systemic increased levels could indicate axonal injury and degeneration [ 39 ].…”
Section: Salivary Biomarkersmentioning
confidence: 99%
“…Since 2020, a handful of (pre)clinical studies investigated the correlation between NfL levels and seizures as well. [13][14][15][16][17][18] Lybeck et al showed that patients with electrographic SE, due to brain injury after cardiac arrest, had elevated serum NfL levels compared to patients who did not develop SE after cardiac arrest. They suggest a correlation of SE with the development of additional secondary neuronal injury, predicted by higher serum NfL levels.…”
Section: Introductionmentioning
confidence: 99%
“…However, this does not reflect quantification in blood or cerebrospinal fluid (CSF). Since 2020, a handful of (pre)clinical studies investigated the correlation between NfL levels and seizures as well 13‐18 . Lybeck et al showed that patients with electrographic SE, due to brain injury after cardiac arrest, had elevated serum NfL levels compared to patients who did not develop SE after cardiac arrest.…”
Section: Introductionmentioning
confidence: 99%